Natural Radioactivity And Radon Concentration In Tapioca And Sweet Potato In Kedah And Pulau Pinang: Transfer Factor And Radiological Risks - Muidh S, Almutairi Abdulmajeed (2022)
Soil is the principal reservoir of natural radionuclides that can be transmitted via the food chain to humans. In this work, the activity concentrations of 226Ra, 232Th and 40K in soil, tapioca and sweet potato, and fertilizer from Penang and Kedah were studied. Measurement of the activity concentrations was made using high purity germanium detector (HPGe). The transfer factors of the radionuclides were determined from soil to root vegetables. The activity concentrations of 226Ra, 232Th and 40K in soil samples from Kedah are 92.46 ± 46.88, 65.59 ± 11.43 and 583.11 ±121.89 Bq kg-1, respectively. The corresponding activity concentration of the samples from Penang are 80.87 ± 9.22, 57.60 ± 4.41 and 512.09 ±113.24 Bqkg-1. The average radionuclide concentrations were significantly higher in Kedah soil than in Penang. Measured values were compared with studies worldwide.